Gambaran Fear Yang Dialami Mahasiswa Prokrastinator Yang Sedang Mengerjakan Skripsi - Suci Nugraha; Lilim Halimah; Farida Coralia (SCHEMA (Journal of Psychological Research), 2011)
Most students of 2005 class can complete the regular lectures on time and signed thesis in 8th semester, but only 3 of 35 students who could complete the thesis for a semester. This problem is not caused by poor ability due to delay completion of task. Delay the completion of the task behavior is known as procrastination. Burka and Yuen (2008) states that procrastination is caused by a sense of fear which classified into five forms, namely fear of failure, fear of success, fear of losing the battle, fear of separation and fear of intimacy. By using the procrastination Scale given to 50 students class of 2005 who are working on thesis obtained the result that 64% of them include procrastinator. The group of procrastinator students known that 78% felt the fear of failure and fear of success. Two form of fear are the most widely fear perceived by most procrastinator students.